Investigating the Relationship between Organizational Memory and Management of Organizational Conflicts in Chaharmahal and Bakhtiari Social Security Staff - Meisam Jamalzadeh (Journal of Global Pharma Technology, 2017)
Human resources, the most important and valuable factor, are from different sources of organization and conflict is a phenomenon that has positive and negative effects on the performance of individuals and organizations. The ability to deal with the conflict and its management is of a great importance to the success of the managers of the organizations. Therefore, the purpose of this study is to investigate the relationship between organizational memory and management of organizational conflicts among Chaharmahal and Bakhtiari social security staff. The research method is descriptive and survey method. The statistical population of this research includes all employees of Chaharmahal and Bakhtiari social security and the sample is 150 with Cochran formula. For measuring the variables, a researcher-made organizational memory questionnaire and Stefan Robbins organizational conflict management questionnaire were used. The reliability of the questionnaires was calculated using Cronbach's alpha method and validity of the questionnaire is confirmed by content method. Pearson correlation coefficient was used to analyze the data using SPSS 19 software. The results showed that there is a significant positive correlation between 5 components of organizational memory (personal skills, mental models, organization structure, data retrieval and information recording) and management of organizational conflicts among Chaharmahal and Bakhtiari social security staffs.Keywords: Organizational memory, Management of organizational conflicts, Social security organization.